Receptor for Activated C Kinase1B (RACK1B) Delays Salinity-Induced Senescence in Rice Leaves by Regulating Chlorophyll Degradation - Md Ahasanur Rahman; Hemayet Ullah (Plants, 2023)
The widely conserved Receptor for Activated C Kinase1 (RACK1) protein is a WD-40 type scaffold protein that regulates diverse environmental stress signal transduction pathways. Arabidopsis RACK1A has been reported to interact with various proteins in salt stress and Light-Harvesting Complex (LHC) pathways. However, the mechanism of how RACK1 contributes to the photosystem and chlorophyll metabolism in stress conditions remains elusive. In this study, using T-DNA-mediated activation tagging transgenic rice (Oryza sativa L.) lines, we show that leaves from rice RACK1B gene (OsRACK1B) gain-of-function (RACK1B-OX) plants exhibit the stay-green phenotype under salinity stress. In contrast, leaves from down-regulated OsRACK1B (RACK1B-UX) plants display an accelerated yellowing. qRT-PCR analysis revealed that several genes which encode chlorophyll catabolic enzymes (CCEs) are differentially expressed in both RACK1B-OX and RACK1B-UX rice plants. In addition to CCEs, stay-green (SGR) is a key component that forms the SGR-CCE complex in senescing chloroplasts, and which causes LHCII complex instability. Transcript and protein profiling revealed a significant upregulation of OsSGR in RACK1B-UX plants compared to that in RACK1B-OX rice plants during salt treatment. The results imply that senescence-associated transcription factors (TFs) are altered following altered OsRACK1B expression, indicating a transcriptional reprogramming by OsRACK1B and a novel regulatory mechanism involving the OsRACK1B-OsSGR-TFs complex. Our findings suggest that the ectopic expression of OsRACK1B negatively regulates chlorophyll degradation, leads to a steady level of LHC-II isoform Lhcb1, an essential prerequisite for the state transition of photosynthesis for adaptation, and delays salinity-induced senescence. Taken together, these results provide important insights into the molecular mechanisms of salinity-induced senescence, which can be useful in circumventing the effect of salt on photosynthesis and in reducing the yield penalty of important cereal crops, such as rice, in global climate change conditions.